Exposition of hepatitis B surface antigen (HBsAg) on the surface of HEK293T cell and evaluation of its expression - Mina Mirian; Razieh Taghizadeh; Hossein Khanahmad; Mansour Salehi; Ali Jahanian-Najafabadi; Hojjat Sadeghi-aliabadi; Shirin Kouhpayeh (Wolters Kluwer Medknow Publications, 2016)
Hepatitis B virus (HBV) is considered as a global health concern and hepatitis B surface antigen (HBsAg) is the most immunogenic protein of HBV. The purpose of this study was to evaluate the expression of HBsAg on the cell surface of human embryonic kidney cell line (HEK293T). After transformation of expression vector pcDNA/HBsAg to E.coli TOP10F', plasmid was extracted and digested with BglII. Afterwards, the linearized vector was transfected to cells and treated with hygromycin B for 5 weeks to expand the resulted clonies. The permanent expression of HBsAg followed by flow cytometry uptill now about one year. Genomic DNA was extracted from transfected cells and the existence of HBsAg gene was assessed by PCR. Real-time RT-PCR was utilized to measure the expression at the RNA level and flow cytometery was carried out to assess protein expression. Insertion of HBsAg cDNA in HEK293T genome was confirmed by PCR. The results of real-time RT-PCR illustrated that each cell expresses 2275 copies of mRNA molecule. Flow cytometry showed that compared with negative control cells, 99.9% of transfected cells express HBsAg on their surface. In conclusion, stable expression of hepatitis B surface antigen on the membrane of HEK293T provides an accurate post-translational modification, proper structure, and native folding in contrast with purified protein from prokaryotic expression systems. Therefore, these exposing HBsAg cells are practical in therapeutic, pharmaceutical, and biological sets of research.